2021
DOI: 10.3390/molecules26175118
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Effect of Benzimidazole Derivatives, Especially Mebendazole, on Triple-Negative Breast Cancer (TNBC) and Radiotherapy-Resistant TNBC In Vivo and In Vitro

Abstract: In this study, we aimed to evaluate the anticancer effect of benzimidazole derivatives on triple-negative breast cancer (TNBC) and investigate its underlying mechanism of action. Several types of cancer and normal breast cells including MDA-MB-231, radiotherapy-resistant (RT-R) MDA-MB-231, and allograft mice were treated with six benzimidazole derivatives including mebendazole (MBZ). Cells were analyzed for viability, colony formation, scratch wound healing, Matrigel invasion, cell cycle, tubulin polymerizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…In our previous study, MBZ hardly affected cell viability at doses of 0.01, 0.1, 0.5, 1, 2, 5, and 10 μM for 24 h in MDA-MB-231 cells and RT-R-MDA-MB-231 cells. However, when incubated for 72 h after 10 μM of MBZ administration, cell viability was slightly decreased by approximately 35–50% compared to the control [ 9 ]. Based on this result, 10 mg/kg of MBZ was tested for in vivo study and showed no hepatic damage, kidney toxicity, or body weight loss, but exhibited a significant decrease in tumor volume and lung metastasis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study, MBZ hardly affected cell viability at doses of 0.01, 0.1, 0.5, 1, 2, 5, and 10 μM for 24 h in MDA-MB-231 cells and RT-R-MDA-MB-231 cells. However, when incubated for 72 h after 10 μM of MBZ administration, cell viability was slightly decreased by approximately 35–50% compared to the control [ 9 ]. Based on this result, 10 mg/kg of MBZ was tested for in vivo study and showed no hepatic damage, kidney toxicity, or body weight loss, but exhibited a significant decrease in tumor volume and lung metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…In the field of oncology, research is being conducted to supplement existing treatments for various cancers by harnessing the anticancer effect of anthelmintics [ 8 ]. In a previous study, we found that MBZ alone had anticancer effects in RT-resistant TNBC by inducing apoptosis and cell cycle arrest, suppressing the expression of cancer stem cell markers (CD44 and OCT3/4), and inhibiting cancer progression-related ESM-1 proteins [ 9 ]. Herein, we found that the coadministration of MBZ and RT increased the anticancer effect in RT-resistant TNBC compared to MBZ or RT individual regimens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MBL shows direct cytotoxic action, yet in addition synergizes with radiation and different chemotherapeutic specialists, and animates the counter cancer resistant reaction in the body, Studies have shown that MBL fundamentally makes harm the DNA of a disease cell, hence halting its development and it its spread to decrease. (7,8) .…”
Section: Introductionmentioning
confidence: 99%